The effectiveness of exercise snacks as a time-efficient treatment for improving cardiometabolic health in adults: a systematic review and meta-analysis - Chen, Jiping; Lu, Yanyu; Zhao, Haojie; Liu, Haojie; Yao, Jiawei (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesExercise snacks (ES) are short bursts of intensive exercise done at regular intervals during the day. The benefits to cardiometabolic health of ES for adults are unclear. The present meta-analysis aimed to assess the effects of ES on cardiometabolic health in adults.MethodsA systematic search was conducted in accordance with the PRISMA guidelines, using the following databases: PubMed, Web of Science, The Cochrane Library, EBSCOhost, and Embase, spanning all previous years up to May 24, 2025. The included studies were evaluated for their literature quality using the effective public health practice project quality assessment tool. The data were analyzed using a random-effects meta-analysis.Results27 studies with a total of 970 participants were included in this meta-analysis. There was a significant beneficial effect of ES on maximal oxygen uptake [SMD (standard mean difference) = 0.63; 95% CI: 0.45, 0.82; P < 0.001], body fat percentage (SMD = −0.21; 95% CI: −0.38, −0.04; P = 0.02), waist circumference (SMD = −0.21; 95% CI: −0.42, −0.00; P = 0.05), systolic blood pressure (SMD = −0.67; 95% CI: −0.98, −0.37; P < 0.001), diastolic blood pressure (SMD = −0.34; 95% CI: −0.65, −0.04; P = 0.03), fasting blood glucose (SMD = −0.40; 95% CI: −0.79, −0.02; P = 0.04), high-density lipoprotein (SMD = 0.26; 95% CI: 0.07, 0.46; P = 0.01), low-density lipoprotein (SMD = −0.30; 95% CI: −0.56, −0.04; P = 0.02), and total cholesterol (SMD = −0.39; 95% CI: −0.68, −0.10; P = 0.01). There are no statistically effects of ES on body mass (SMD = −0.094; 95% CI: −0.261, 0.072; P = 0.267) and triglycerides (SMD = −0.193; 95% CI: −0.478 to 0.093; P = 0.187). Furthermore, no significant risk of publication bias was observed for any outcomes.ConclusionThis comprehensive meta-analysis provides robust evidence that ES, characterized by brief, intensive bouts of activity interspersed throughout the day, offer significant and clinically meaningful benefits for improving multiple facets of cardiometabolic health in adults.